2004
DOI: 10.1063/1.1753056
|View full text |Cite
|
Sign up to set email alerts
|

Persistent photocurrent and surface trapping in GaN Schottky ultraviolet detectors

Abstract: GaN-based Schottky detectors were implemented and their photoresponse as a function of the incident power and time was measured. The measured photoresponse shows gain saturation and persistent photoconductivity behavior. These effects are shown here to be related to each other, arising from a nonideal semiconductor surface. A microscopic model of the gain mechanism to explain these observations is presented. Trap density at the semiconductor metal interface, characteristic lifetime, and carrier capture coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
76
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 13 publications
5
76
0
Order By: Relevance
“…The upper spectrum shows the peak photocurrent at a bias of +40 V, the lower at +20 V and the lowest is reverse biased at -20 V. Inset in the figure is a screen capture of the typical temporal response to the FEL pulse. Let us note from the inset figure that the induced photocurrent decays with over a millisecond time scale, the FEL pulse length is 10 µs and the observed persistent photocurrent is almost certainly due to trapping in the contact layer region as has previously been observed [8]. It can be seen from the spectra that the device exhibits a broad band response to the infrared excitation.…”
Section: Methodsmentioning
confidence: 59%
“…The upper spectrum shows the peak photocurrent at a bias of +40 V, the lower at +20 V and the lowest is reverse biased at -20 V. Inset in the figure is a screen capture of the typical temporal response to the FEL pulse. Let us note from the inset figure that the induced photocurrent decays with over a millisecond time scale, the FEL pulse length is 10 µs and the observed persistent photocurrent is almost certainly due to trapping in the contact layer region as has previously been observed [8]. It can be seen from the spectra that the device exhibits a broad band response to the infrared excitation.…”
Section: Methodsmentioning
confidence: 59%
“…It is also observed that the off-current decays slowly, which was attributed to the persistent photocurrent arising from charged surface trap states, and is an effect previously found in other binary semiconductor nanowires. [33][34][35][36][37] The performance of a photodetector is also determined by its total responsivity, [ 38 ] as shown in Figure 3 d, which is defi ned as…”
Section: Cdse/znte Core/shell Nanowire Array Photodetector Under Bluementioning
confidence: 99%
“…This material is also remarkably tolerant to aggressive environments, due to its thermal stability and radiation hardness. To date, several groups have reported encouraging results for nitride-based photodetectors, such as p-n junction diode [1,2], p-i-n detectors [3][4][5][6], p-p-n diode [7], Schottky barrier detectors [8][9][10] and metal-semiconductor-metal (MSM) detectors [11][12][13][14][15][16][17][18][19]. Among these structures, Schottky-barrier detectors are an attractive choice for UV detectors, given their fabrication simplicity and much faster response speed.…”
Section: Introductionmentioning
confidence: 99%